PENGARUH PARTISIPASI PENGANGGARAN PADA KINERJA PEMERINTAH DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI - prihantini, candra maha; erawati, ni made adi (E-Jurnal Akuntansi; Vol 11 No 2 (2015), 2015)
Budgeting is a political process in which the public sector budget should be informed to the public to be criticized , discussed and given input . The porpused of the aim is to found determinend the effect of budget participation in the appereance of local government officials , as well as to determine the moderating effect of organizational commitment in budgeting participation in the work of local government officials in the city government Denpasar. The Populations in this study amounted to sixteen offices in City Government Denpasar with the respondent amounted to 68 peoples . Data collected by using a questionnaire . Method of determining the sample is purposive sampling by using certain criteria in its collection . This study tested using moderation regression analysis with the program SPSS.The resultsof analysis show that budgetary participation and significant positive effecst in the appereance of local government officials as well as the commitment to strengthen the organization is able to moderate  of budget participation on the appereance of local government officials .
Keywords: participation budgeting, appereance of local government officials, organizational commitment